Pengaruh Model Problem Based Learning Terhadap Hasil Belajar Bahasa Indonesia Kelas III SD Negeri Sendangguwo 01 - Nila Pramesti Rahayu; Aries Tika Damayani; Khafidlotur Rofiqoh; Sugiyanti Sugiyanti (Journal on Education, 2024)
This research is motivated by low student learning outcomes and learning that is still teacher-centered making students appear inactive in learning. This research aims to determine the effect of using the Problem Based Learning (PBL) model on students' Indonesian language learning outcomes in Transportation Technology Development material for class III SDN Sendangguwo 01. This research uses a quantitative approach, experimental methods with the research type Pre-Experimental Designs, One-Group Pretest design. -Posttest Design. Sampling used a total sampling technique with 28 class III students at SDN Sendangguwo 01. The results of pretest and posttest data analysis on transportation technology material using the Problem Based Learning (PBL) model showed that the average pretest score was 44,64, while the students' posttest was 76,43. The results of hypothesis testing with paired samples t-test statistics obtained a significance value (2-tailed) of 0.000<0.05, thus it can be concluded that there is an influence of the use of the Problem Based Learning (PBL) model on the results of learning Indonesian for class III at SDN Sendangguwo 01.